Occupational Health and Safety (OHS) Analysis at The PG Kremboong Production Department using The Risk Priority Number and 5 Whys Method - Yoniv Erdhianto (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2021)
Occupational Health Safety (OHS) is not only important for improving the social security and welfare of its workers but far from that, K3 has a positive impact on the sustainability of employee work productivity. In term of safety, the production department of PG Kremboong still bring some risks that may cause work accidents, such as the leaks in the evaporator and juice heater body that frequently happened in the processing department. The hazard identification assessment uses the RPN (Risk Priority Number) method where each risk-causing factor is assessed by its value of severity, frequency or probability (occurrence), and detection, then illustrated with a Pareto Diagram to determine the most dominant problem. and using the five why's analysis method to analyze the root causes of the problem in order to obtain a solution. The most dominant risk in PG. KREMBOONG is a leak in the evaporator body that hits the worker and a leak in the juice heater body, based on RPN values which reached 36 and 27.